Designing Engaging Learning Activities in MOOC: A Success Story - Syahrul Nizam, Junaini; Johari, Abdullah; Yanti Rosmunie, Bujang; Ahmad Hadinata, Fauzi; Jonathan, Sidi (Universiti Malaysia Sarawak, (UNIMAS), 2016)
The booming era of e-learning has evolved over the past decade. Massive Open Online Courses (MOOCs) has revolutionized as the in-thing that offer richer, wider, and connected learning experiences. MOOCs have made an interesting splash on online education canvas especially after Coursera, Udacity, and edX have become the main player in the industry. This article presents a brief success story of the implementation of homemade MOOC for TMU1043 Multimedia Technology course during semester 1, 2015/2016. We also discuss how we designed engaging learning activities on our MOOC. In the future work section, we discuss a plan of a Scholarship of Teaching and Learning (SoTL) research that we are going to conduct based on our MOOC.